Purchase Procrastination Behavior in Social Commerce: Influence of Pre-Purchase Cognitive Structures among Generation Z Consumers - Ni Wayan Cantika Maharani; Putu Dyah Permatha Korry; Kadek Wulandari Laksmi P; I Gusti Ngurah Oka Ariwangsa (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The growth of social media has changed consumer purchasing behavior, with Generation Z often delaying purchase decisions despite having easy access to product information, reviews, and recommendations through social commerce. This study aims to examine the factors that influence purchase delay behavior among Generation Z in the context of social commerce. This study employs a quantitative causal-associative design, collecting data through surveys and analyzing them using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings demonstrate that exposure to live streams on TikTok Shop plays a crucial role in triggering purchase delay behavior among Generation Z consumers in Bali Province. The higher the intensity of live stream exposure, the greater consumers’ tendency to postpone purchase decisions as they conduct a more in-depth product evaluation. Live stream exposure also increases product comparison behavior and strengthens the influence of the social environment in the decision-making process. Additionally, product comparison behavior and the influence of the social environment were found to increase the tendency toward purchase postponement. Consumers tend to compare various product alternatives and consider reviews, comments, and recommendations from their social environment before deciding to buy. These two variables were also found to mediate the influence of live stream exposure on purchase postponement behavior.